PENINGKATAN KETERAMPILAN BERBICARA MELALUI MODEL NUMBERED HEAD TOGETHER KELAS V SDN 03 PONTIANAK KOTA - Aping, Marselina; Kaswari, Kaswari; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract; The general problem of this research is, "Is the Numbered Head Together model able to improve the speaking skill of grade V students of Pontianak City State Elementary School?" This research aimed to improve the students' speaking skill by using Numbered Head Together model on grade V students of Pontianak State Elementary School City. This form of research is a classroom action research with collaborative nature. The place of this research is at State Elementary School 03 Pontianak City. Subject of the research teacher and all students of class V which amounted to 30 people. Technique collecting data used is Observation and observation of document with tool in the form of observation sheet and document scrutiny sheet. This research was conducted in 3 cycles with the final result of research on the relevant content aspect, systematic organization, word accuracy and polite language and the smoothness obtained in cycle I as many as 8 people or 26.67% in cycle II as many as 15 people or about 55, 56% increased by 28.89% from cycle I, and in cycle III as many as 22 people or about 78.57% increased by 23.01% from cycle II.Based on the data obtained can be concluded there is an increase in each cycle.Â Keywords: Improved, speaking skills, model numbered head together.